2010
DOI: 10.1016/j.jsat.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of motivation for abstinence at the end of outpatient substance abuse treatment

Abstract: Commitment to abstinence, a motivational construct, is a strong predictor of reductions in drug and alcohol use. Level of commitment to abstinence at treatment end predicts sustained abstinence, a requirement for recovery. This study sought to identify predictors of commitment to abstinence at treatment end to guide clinical practice and to inform the conceptualization of motivational constructs. Polysubstance users (N = 250) recruited at the start of outpatient treatment were re-interviewed at the end of serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 58 publications
1
71
1
1
Order By: Relevance
“…In contrast, however, Laudet and Stanick (2010), in a study of motivation to change framed as "commitment to abstinence," found that male gender was a negative correlate of motivation to change (Laudet and Stanick, 2010). In the subanalysis, female gender was correlated with treatment history, end of treatment experience, quality-of-life satisfaction, and the outcome variable commitment to abstinence (Laudet and Stanick, 2010).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, however, Laudet and Stanick (2010), in a study of motivation to change framed as "commitment to abstinence," found that male gender was a negative correlate of motivation to change (Laudet and Stanick, 2010). In the subanalysis, female gender was correlated with treatment history, end of treatment experience, quality-of-life satisfaction, and the outcome variable commitment to abstinence (Laudet and Stanick, 2010).…”
mentioning
confidence: 95%
“…In the subanalysis, female gender was correlated with treatment history, end of treatment experience, quality-of-life satisfaction, and the outcome variable commitment to abstinence (Laudet and Stanick, 2010). In a study that examined early intervention for alcohol use, Freyer et al (2004) also found that women reported higher preparedness to seek help relative to male counterparts.…”
mentioning
confidence: 96%
“…Deciding to research motivation and the correlates of it results from the fact, well documented by empirical research, that motivation (in particular, the internal one) is one of the strongest predictors of the results of psychotherapy, including in the case of alcohol-dependent individuals (cf. Chodkiewicz, 2012Chodkiewicz, , 2013aCooper, 2010;Laudet & Stanick, 2010). In spite of that, motivation has been devoted relatively little space in research into alcohol-dependent individuals to date; the symptom of that way of thinking is, in accordance with the opinion of Groshkova (2010), the fact that no coherent model including external and internal factors influencing the motivation and the changes in it in the case of alcoholics has been developed yet.…”
Section: Andó Et Al 2012mentioning
confidence: 99%
“…Positive social support networks are key to supporting those in recovery (Best et al 2015a, b;Litt et al 2009;Stevens et al 2010;Timpson et al 2016). High levels of social support are associated with decreased levels of relapse (Granfield and Cloud 2001;Laudet et al 2006); improved resilience to stress, depression, anxiety, social isolation, and stigma (Best et al 2015a, b;Hester et al 2013); enhanced subjective well-being (Laudet et al 2006); and improved quality of life (Laudet and Stanick 2010;Mericle 2014). Peers and social networks are also integral to the generation of recovery capital (Timpson et al 2016).…”
Section: Introductionmentioning
confidence: 99%